Strukturen des Affektiven: Kulturelle Ordnungen, Aufmerksamkeiten und affektive Hintergründe - Dahms, Susann (transcript, 2019)
An extended view of various affective phenomena and cultural orders from a sociological perspective. What role does predisposed attention play in this?